PENGEMBANGAN TEKNIK TRANSFORMASI PUISI BALADA DALAM PENULISAN TEKS DRAMA SISWA KELAS XI SMK FARMASI TENGGARONG - NFN Supriyanti (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2017)
This study aimed to make a lesson plan (RPP) and a textbook. The research method used was Research and Development (R&D) with Borg & Gall development model . The trials were given to small groups and large group . The techniques applied to collect the data were observation, interview, and test . The data were analyzed using descriptive and descriptive quantitative statistics . The learning model and teaching materials of writing drama text with ballad poem transformation techniques effectively improve students’ learning outcome. The learning outcome of the small groups went up from 67 .16% to 87 .16% with a standard deviation of 8 .51 and the large group’s increased from 67,67% to 89% with standard deviation 18,42% .